Relationship Between Accelerometer-Based Physical Activity, Sedentary Behavior, and Mental Health in Young Finnish Men - Appelqvist-Schmidlechner, Kaija; Raitanen, Jani; Vasankari, Tommi; Kyröläinen, Heikki; Häkkinen, Arja; Honkanen, Tuomas; Vaara, Jani P. (Frontiers in Public Health, 2022)
Healthy lifestyle behaviors including physical activity (PA) have been recognized to contribute positively to mental health. Most of the evidence on relationship between PA and mental health relies on self-reported PA results. Device-based measures on PA or sedentary behavior (SB) are less frequently used in mental health research. The present study aimed at examining the relationship between mental health and PA/SB measured by accelerometers in young Finnish men. The sample consisted of 409 men (mean age 28 ± 7 years), who participated in the military refresher training in Finland. Self-rated mental health was measured with Mental Health Inventory (MHI-5) and short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS) measuring mental health both from the perspective of mental health problems and mental well-being. PA was measured with accelerometer from the perspective of light, moderate, vigorous, and total activity, as well as SB. Linear regression models and compositional analysis were applied. Age, education, marital status, employment status, BMI, alcohol use and smoking were used as covariates. Evidence on relationship between total PA (standardized regression coefficient 0.340; 95% CI 0.022–0.657, p = 0.036) and SB (standardized regression coefficient −0.340; 95% CI −0.657 to −0.022, p = 0.036) with symptoms of mental health problems was found after adjusting for age, education, marital and employment status. The relationship was marginally significant (p = 0.056) after adjusting also for BMI, alcohol use and smoking. No evidence on relationship between PA or SB and mental well-being was found, neither in standard linear regression analysis nor in compositional approach. In our sample of young adult men, PA seemed to have a stronger relationship with symptoms of mental health problems rather than with mental well-being. The findings lead to a conclusion that all PA per se may not be independently associated with mental well-being in young adult males and raise the question whether the domain of PA and its context play a critical role in these relationships.